2019
DOI: 10.1111/jgs.16218
|View full text |Cite
|
Sign up to set email alerts
|

Passive Digital Signature for Early Identification of Alzheimer's Disease and Related Dementia

Abstract: OBJECTIVES Developing scalable strategies for the early identification of Alzheimer's disease and related dementia (ADRD) is important. We aimed to develop a passive digital signature for early identification of ADRD using electronic medical record (EMR) data. DESIGN A case‐control study. SETTING The Indiana Network for Patient Care (INPC), a regional health information exchange in Indiana. PARTICIPANTS Patients identified with ADRD and matched controls. MEASUREMENTS We used data from the INPC that includes st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Missing cognitive data, particularly when heightened among demographic subsets, affects not only quality of patient care, but also quality of EHR databases increasingly used for research and clinical decision‐making algorithms. Researchers have developed models to identify patients with high risk of AD using various EHR data including the presence of cognitive symptoms in EHR 19–21,37 . Suboptimal data inputs reduce the accuracy and generalizability of EHR‐based models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Missing cognitive data, particularly when heightened among demographic subsets, affects not only quality of patient care, but also quality of EHR databases increasingly used for research and clinical decision‐making algorithms. Researchers have developed models to identify patients with high risk of AD using various EHR data including the presence of cognitive symptoms in EHR 19–21,37 . Suboptimal data inputs reduce the accuracy and generalizability of EHR‐based models.…”
Section: Discussionmentioning
confidence: 99%
“…We further examined whether the likelihood of having a documented cognitive measure differed by patient age, sex, race, comorbidities, and health‐care use. These results are also informative of the quality and missingness in EHR data, which is increasingly used to develop algorithms to predict incidence of dementia and conduct embedded pragmatic clinical trials 19–22 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the incidence of AD has been reported to be higher in those individuals with lower education (16). Previous studies showed that digital health data, cognitive performance such as memory, and neuropsychiatric symptoms can help identify those with dementia from normal subjects (17)(18)(19)(20)(21). Some research groups (19) have suggested that a diagnosis of dementia can be made from health recording data.…”
Section: Discussionmentioning
confidence: 99%
“…In [45], Jammeh et al also evaluated different ML algorithms for AD screening using clinical data and diagnosis records. Boustani et al used electronic medical record data to develop a passive digital signature for early identification of AD through logistic regression [46]. In these studies, no variable selection was performed.…”
Section: Machine Learning and Alzheimer's Diseasementioning
confidence: 99%